Contemporary Culinary Trends, Product Innovation, and Purchase Decisions in Public Culinary Spaces: The Moderating Role of Local Cultural Preferences - Reno Catelya Dira Oktavia; Nurbaeti; Amrullah; Muhammad Bilal Sulaeman; Raka Dimas Wisanggeni (Jurnal Ilmiah Hospitality Management, 2026)
This study addresses the main problem of whether contemporary culinary trends truly drive purchase decisions in local public culinary spaces compared to product innovation and cultural factors. The study aims to analyze the influence of contemporary culinary trends and product innovation on purchase decisions, with local cultural preferences as a moderating variable. Previous studies have generally emphasized the positive role of culinary trends and innovation; however, they remain limited in examining the inconsistency of these effects and the moderating role of local cultural preferences in public space contexts. A quantitative approach was employed through a survey of 110 respondents using purposive sampling, and the data were analyzed using SEM-PLS. The findings reveal that product innovation and local cultural preferences significantly influence purchase decisions, while contemporary culinary trends do not. Furthermore, local cultural preferences do not act as a moderator. Theoretically, this study contributes by highlighting the dominance of cultural identity in consumer behavior, indicating that purchase decisions are more culturally driven than trend-driven.